The economics of football - Dobson, Stephen; Goddard, John A. (New York : Cambridge University Press, 2001)
An original economic analysis of professional football. Uses theoretical and empirical methods to consider role of owners, managers, players and spectators. Concludes with an extended discussion of key policy issues, including European super league proposals, contractual arrangements in the players' labour market, and football's evolving relationship with the broadcasting media.
Cover; Half-title; Title; Copyright; Dedication; Contents; Figures; Tables; Preface; Acknowledgements; 1 Introduction; 2 Professional football: historical development and economic structure; 3 Competitive balance and uncertainty of outcome; 4 The labour and transfer markets; 5 The contribution of the football manager; 6 Managerial change and team performance; 7 The demand for football attendance; 8 Information transmission and efficiency: share prices and fixed-odds betting; 9 Professional football: current issues and future prospects; References; Index.
Includes bibliographical references (pages 440-451) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Soccer -- Economic aspects -- Great Britain; Soccer -- Great Britain -- Finance; Football -- Aspect économique -- Grande-Bretagne.; Football -- Grande-Bretagne -- Finances; BUSINESS & ECONOMICS -- Industries -- General; Soccer -- Economic aspects; Soccer -- Finance; Great Britain; Samfundsvidenskab -- Økonomi; Electronic book; Electronic books